Comments on the Eslicarbazepine Acetate Section of the Article 'Therapeutic Drug Monitoring of the Newer Anti-Epilepsy Medications' - Patricio Soares-; Ahmet H. Öztiryaki (MDPI AG, 2010)
The recent review of Matthew D. Krasowski on 'Therapeutic Drug Monitoring of the Newer Anti-Epilepsy Medications' is a useful foundation of comparative interpretations on our current knowledge about therapeutic drug monitoring. Within the review, the statement that therapeutic drug monitoring has a minimal role in the therapeutic use of eslicarbazepine acetate due to its relatively predictable pharmacokinetics reflects the existing body of evidence although some information such as eslicarbazepine acetate's chemical structure, proportions of its metabolites, their pharmacokinetics and chiral method of plasma level measurement need to be revised. These critical characteristics differentiate the novel compound from former dibenzazepines such as carbamazepine and oxcarbazepine in its clinical effects and needs for therapeutic drug monitoring.